Magnetopause Standoff Position Changes and Geosynchronous Orbit Crossings: Models and Observations - Y. M. Collado‐Vega; P. Dredger; R. E. Lopez; S. Khurana; L. Rastaetter; D. Sibeck; M. Anastopulos (Space Weather)
Abstract This research examines the ability of current physics‐based models to predict the magnetopause location. We use the Run‐On‐Request capabilities at the Community Coordinated Modeling Center at NASA GSFC with 4 magnetohydrodynamic (MHD) models. The magnetopause position prediction and response time to the solar wind changes is then compared to extreme solar wind conditions where magnetopause crossing of geosynchronous orbit have been observed by the Geostationary Operational Environmental Satellite (GOES) satellites. Rigorous analysis/comparison of observations and models is critical in determining magnetosphere dynamics for model validation. This paper is a preliminary effort defining the metrics necessary to understand the current magnetosphere model capabilities and challenges. Results show that there are discrepancies between the MHD models' standoff positions of the dayside magnetopause for the same solar wind conditions on events that included (a) an increase in solar wind dynamic pressure and a step function in the Interplanetary Magnetic Field Bz component; (b) nominal solar wind conditions (values of approximated 400 km/s for solar wind speed and 5 nT for the magnetic field magnitude) with a northward IMF; and (c) compression caused by several coronal mass ejections impacting the near Earth environment. Overall, the models predicted different magnetopause subsolar locations sometimes in the order of 3 RE. Contingency tables were calculated to show model performance in comparison with the data observed with the GOES 13/15 geosynchronous orbit for extreme events and skill scores were calculated.